2012
DOI: 10.4236/jbise.2012.59066
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of NGF in human sperm motility

Abstract: Motility is an important physiological characteristic of a mature sperm. Nerve growth factor (NGF) is a key protein for the survival, maintenance and development of the central and peripheral nervous systems. It has been shown that NGF and its receptors TrkA and p75 are widely expressed in the testis, accessory reproductive organ, and the epididymal sperms. These observation have shifted the attention to the role of NGF on male reproductive physiology. In the present study, we found that NGF remarkably increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
1
15
1
Order By: Relevance
“…; Shi et al. ). The wild rabbit is a seasonal breeder with the peak of reproductive activity occurring in the spring and early summer.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Shi et al. ). The wild rabbit is a seasonal breeder with the peak of reproductive activity occurring in the spring and early summer.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the male, NGF and its two receptors were reported to be expressed in the testis, prostate gland and seminal vesicle of rabbit, suggesting a possible role of this factor in the testicular development and spermatogenesis (Maranesi et al 2015). Furthermore, there are some evidences of the involvement of this protein in sperm motility as it has been observed that exogenous NGF stimulates the motility in a timeand dose-dependent manner (Jin et al 2010;Shi et al 2012). The wild rabbit is a seasonal breeder with the peak of reproductive activity occurring in the spring and early summer.…”
Section: Discussionmentioning
confidence: 99%
“…In the sperm cell, the presence of β‐NGF in the middle piece could also be related to sperm motility. Studies performed on ejaculated sperm (e.g., bovine (Li et al, ), human (Shi et al, )), and sperm from epididymis (golden hamster (Jin et al, )) demonstrate that sperm motility increases in a time‐ and dose‐dependent manner when β‐NGF is added to the sperm culture medium. It is worthy to distinguish that in camelids, ejaculated sperm lack of progressive motility, having only oscillatory movement (Giuliano, Director, Gambarotta, Trasorras, & Miragaya, ); whereas sperm collected form epididymis display forward progressive motility (Morton, Bathgate, Evans, & Maxwell, ).…”
Section: Discussionmentioning
confidence: 99%
“…NGF, an antioxidant supplement, is a member of neurotrophins which has reported to play an important role in the male reproductive system and sperm function [ 11 15 ]. NGF stimulates sperm motility [ 12 , 16 , 17 ], viability [ 13 ] and facilitates sperm cell acrosome reactions [ 12 ], and also play an important role in the proliferation and differentiation of leydig cells and testosterone production [ 18 ].…”
Section: Introductionmentioning
confidence: 99%